Congenital transmission of toxoplasma gondii in ovine - Dos Santos, Thaís Rabelo [UNESP] (2013)
Toxoplasma gondii is a member of the phylum Apicomplexa, order Coccidia, and is an obligate intracellular protozoan parasite that infects humans and several vertebrate hosts. In its life cycle, T. gondii has three infectious forms: the sporozoites (oocysts), tachyzoites (individually or in groups) and bradyzoites (tissue cysts). Toxoplasmosis is a zoonosis of major spread worldwide. Sheep toxoplasmosis was first described by Olafson and Monlux (1942) in the United States.These authors reported this disease in a female who presented neurological symptoms, hyperthermia, muscle rigidity, and other clinical signs. The diagnosis was made after necropsy and histopathological examination of the brain and spinal cord of the animal. In small ruminants, toxoplasmosis is relatively common, responsible for reproductive problems, generating great economic losses in sheep flocks, where the infection is the main cause of abortions, fetal malformations, premature births and neonatal deaths being the main route of infection the ingestion of sporulated oocysts of the parasite. © 2013 by Nova Science Publishers, Inc. All rights reserved.